In vitro evaluation of microbial D- and L-lactate production as biomarkers of infection - Morovic, Paula; Gonzalez Moreno, Mercedes; Trampuz, Andrej; Karbysheva, Svetlana (Frontiers in Microbiology, 2024)
Mammalian cells produce and metabolize almost exclusively L-lactate, bacterial species have the capacity to produce both D-lactate and L-lactate. The aim of this study was to evaluate the intrinsic production of D- and L-lactate in the most common pathogenic microorganisms causing septic arthritis (SA) and periprosthetic joint infection (PJI) as a potential biomarker for the diagnosis of infection. Following microorganisms were grown according to ATCC culture guides and tested for production of D- and L-lactate: Staphylococcus aureus (ATCC 43300), Staphylococcus epidermidis (ATCC 35984), Enterococcus faecalis (ATCC 19433), Streptococcus pyogenes (ATCC 19615), Escherichia coli (ATCC 25922), Pseudomonas aeruginosa (ATCC 27853), Cutibacterium acnes (ATCC 11827), and Candida albicans (ATCC 90028). Pathogens were inoculated in 8 ml of appropriate liquid media and incubated as planktonic or biofilm form in either aerobic, anaerobic or CO2 atmosphere up to 312 h. D- and L-lactate measurements were performed at different time points: 0, 6, 9, 12 and 24 h, then once per day for slow-growing pathogens. Samples were serially diluted and plated for colony counting. Liquid culture media without microorganisms served as a negative control. Production of D-lactate was observed in all tested microorganisms, whereas no L-lactate was detected in E. coli, P. aeruginosa, and C. albicans. Maximal concentration of D-lactate was produced by S. aureus (10.99 mmol/L), followed by E. coli (1.22 mmol/L), and S. epidermidis (0.48 mmol/L). Maximal L-lactate concentration was observed in S. pyogenes (10.12 mmol/L), followed by S. aureus (9.71 mmol/L), E. faecalis (2.64 mmol/L), and S. epidermidis (2.50 mmol/L). S. epidermidis bacterial biofilm produced significantly higher amount of D- and L-lactate compared to planktonic form (p = 0.015 and p = 0.002, respectively). Our study has demonstrated that the most common pathogenic microorganisms causing SA and PJI have the capability to generate measurable amounts of D-lactate in both planktonic and biofilm form, highlighting the practical value of this biomarker as an indicator for bacterial and fungal infections. In contrast to D-lactate, the absence of L-lactate production in certain tested bacteria, as well as in fungi, suggests that L-lactate is not eligible as a biomarker for diagnosing microbial infections.